Impact of Microcredit on Household Consumption and Assets In Nepal (International Journal of Applied Research in Management and Economics, 2023)
This paper intends to assess the impact of microcredit on Household Consumption and Assets in Nepal. The multivariate techniques used to achieve the objectives of the study. The study uses Nepal Living Standard Survey 2011 data, which covers 5,988 households. Considering the endogeneity in the microcredit participation of household, the study uses instrumental variable technique (IV method) for assessing the impact of microcredit on Household Consumption and Assets. After the adjustment of the endogeneity, distance of bank, distance of cooperative from household and holding of land size of household as the instruments, eligible household reduced 475 household from 779 total households of intervention group and similarly 2,953 households from 5,209 total households of control group. CMP (conditional mixed process) estimator used to give flexibility in terms of combining continuous and binary variables together in the same model. Multivariate analysis indicates that it has positive and significant relationship on household consumption and on assets, (household consumption is on Food Consumption, Non-Food Consumption and Total Consumption. And similarly, household assets are, on ownership of livestock such as buffaloes, cows, sheep, etc, Ownership on transportation such as Cycle or Motor cycle, Ownership on appliances, such as Refrigerator, Television, CD player) on intervention group than the control group. The result and finding and review of the literatures in this paper provided a wide range of evidence that microcredit programs can increase incomes and uplift families out of poverty. Microcredit would be a viable and potentially sustainable tool to reduce poverty in Nepal.